A hard carbon material and preparation method thereof, and sodium ion battery
Through multiple heat treatments and doping phosphorus and sulfur elements, and coating with petroleum coke asphalt, the problem of low efficiency of sodium ion batteries for the first time due to the large specific surface area of hard carbon materials is solved, and higher battery efficiency and stability are achieved.
Patent Information
- Application Number
- CN202411688157.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The hard carbon material prepared by lignin has a large specific surface area, which leads to its low first-time Coulomb efficiency in sodium ion batteries.
By performing multiple heat treatments on lignin and mixing with phosphorus, sulfur and petroleum coke asphalt at different temperatures, a cladding layer is formed to reduce the specific surface area and improve the first Coulomb efficiency of sodium ion batteries.
It effectively reduces the specific surface area of hard carbon materials, improves the first Coulomb efficiency of sodium ion batteries, and enhances the stability and conductivity of the battery.
Smart Images

Figure CN119176545B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery materials, and in particular to a hard carbon material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the rapid development of the new energy vehicle industry, the demand for lithium batteries has also increased, but the global lithium resource reserves are limited and unevenly distributed. Therefore, the development of new alternative energy storage devices with high performance and low price has attracted much attention. Since sodium and lithium have similar physical and chemical properties; sodium ion batteries work in a similar way to lithium ion batteries and have abundant resource reserves, they are considered to be a potential substitute for lithium ion batteries.
[0003] Traditional lithium-ion batteries use graphite materials as the negative electrode side, but graphite materials are not suitable for sodium-ion battery systems. Therefore, an important obstacle restricting the rapid development of sodium-ion batteries is the lack of suitable negative electrode materials.
[0004] Hard carbon materials have developed micro-nanostructure pores, large interlayer spacing and abundant defects. Their ordered structures facilitate the embedding and extraction of sodium ions, making them suitable for sodium storage. Lignin has a wide range of sources and abundant production, a high carbon content (about 60%) and a large number of benzene rings, making it a suitable carbon precursor. However, the hard carbon material particles currently prepared from lignin have a large specific surface area, resulting in a low first coulombic efficiency in sodium-ion batteries. Summary of the invention
[0005] The invention provides a method for preparing a hard carbon material, wherein the preparation method can reduce the specific surface area of lignin hard carbon, thereby improving the first coulombic efficiency in a sodium ion battery.
[0006] The present invention also provides a hard carbon material prepared by the preparation method. The hard carbon material is used for a sodium negative electrode, which is beneficial to improving the first coulomb efficiency in a sodium ion battery.
[0007] The present invention also provides a sodium ion battery. Since the electrode sheet of the sodium ion battery includes the hard carbon material, the battery has good stability and conductivity.
[0008] In a first aspect, the present invention provides a method for preparing a hard carbon material, comprising the following steps:
[0009] S1: subjecting lignin to a first heat treatment at 1200° C.-1500° C. to obtain a first hard carbon precursor;
[0010] S2: the first hard carbon precursor is mixed with a phosphorus source and a sulfur source, and the obtained mixed system is subjected to a second heat treatment at 600-800° C. to obtain a second hard carbon precursor;
[0011] S3: The second hard carbon precursor and petroleum coke pitch are mixed, and the resulting mixed system is subjected to a third heat treatment at 320°C - 400°C under the protection of an inert gas, and then subjected to an oxidation treatment in an oxygen-containing atmosphere to obtain a third hard carbon precursor;
[0012] S4: The third hard carbon precursor is subjected to a fourth heat treatment at 1300°C - 1500°C under the protection of an inert gas to obtain the hard carbon material.
[0013] Further, in step S2, the mixing of the first hard carbon precursor, the phosphorus source, and the sulfur source includes the following process:
[0014] The first hard carbon precursor, the phosphorus source, and the sulfur source are ground or stirred to obtain the mixed system;
[0015] Or, the first hard carbon precursor is dispersed in a solvent, then the phosphorus source and the sulfur source are added, impregnation treatment is carried out, and the solid product obtained after solid-liquid separation is dried to obtain the mixed system.
[0016] Further, the phosphorus source is phosphoric acid, disodium hydrogen phosphate, or sodium tripolyphosphate; the sulfur source is thiourea, sodium sulfate, or sodium sulfide;
[0017] And / or, the molar ratio of the carbon element of the first hard carbon precursor, the phosphorus element of the phosphorus source, and the sulfur element of the sulfur source is 100:3:1.
[0018] Further, the Dv50 of the lignin is 3 µm - 15 µm; the Dv50 of the petroleum coke pitch is 2 µm - 7 µm.
[0019] Further, the petroleum coke pitch accounts for 1% - 10% of the mass of the second hard carbon precursor.
[0020] Further, the oxidation treatment includes the following process:
[0021] At a°C, perform a primary oxidation treatment for 1 min - 1 h;
[0022] At b°C, perform a secondary oxidation treatment for 1 h - 3 h;
[0023] At c°C, perform a tertiary oxidation treatment for 3 h - 5 h;
[0024] Wherein, a < b < c; and 150 ≤ a ≤ 200, 200 ≤ b ≤ 300, 300 ≤ c ≤ 400.
[0025] Further, in the atmosphere of the primary oxidation treatment, the oxygen concentration is m, in the atmosphere of the secondary oxidation treatment, the oxygen concentration is n, and in the atmosphere of the tertiary oxidation treatment, the oxygen concentration is f, and m < n < f.
[0026] Furthermore, 5%≤m≤10%, 10%≤n≤20%, 20%≤f≤30%.
[0027] In a second aspect, the present invention provides a hard carbon material obtained by the above preparation method.
[0028] In a third aspect, the present invention provides a battery, comprising an electrode sheet, wherein the electrode sheet comprises the hard carbon material described in the second aspect.
[0029] The preparation method of the present invention can reduce the specific surface area of the hard carbon material, improve the import and output capacity of sodium ions, and thus improve the first coulomb efficiency in the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or related technologies, the following briefly introduces the drawings required for use in the embodiments of the present invention or related technologies. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 This is the SEM image of the hard carbon material prepared in Example 1. DETAILED DESCRIPTION
[0032] In order to enable those skilled in the art to better understand the scheme of the present invention, the present invention is further described in detail below. The specific implementation methods listed below are only for describing the principles and features of the present invention. The examples are only used to explain the present invention and are not intended to limit the scope of the present invention. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0033] In order to solve the problem that the hard carbon material particles prepared from lignin have a large specific surface area, petroleum coke asphalt can be coated on the surface of lignin. However, lignin will release volatiles during the carbonization process, destroying the coating structure; while the soft carbon coating layer generated can reduce the specific surface area of the hard carbon, it will also play a role in isolating and shielding the transmission of sodium ions, thereby failing to effectively improve the first coulomb efficiency of the sodium ion battery. To this end, the present invention adopts the following technical solutions:
[0034] In a first aspect, the present invention provides a method for preparing a hard carbon material, comprising the following steps:
[0035] S1: subjecting lignin to a first heat treatment at 1200° C.-1500° C. to obtain a first hard carbon precursor;
[0036] S2: the first hard carbon precursor is mixed with a phosphorus source and a sulfur source, and the obtained mixed system is subjected to a second heat treatment at 600-800° C. to obtain a second hard carbon precursor;
[0037] S3: the second hard carbon precursor and petroleum coke pitch are mixed, and the obtained mixed system is subjected to a third heat treatment at 320° C.-400° C. under the protection of an inert gas, and then subjected to an oxidation treatment in an atmosphere containing oxygen to obtain a third hard carbon precursor;
[0038] S4: The third hard carbon precursor is subjected to a fourth heat treatment at 1300° C.-1500° C. under the protection of an inert gas to obtain the hard carbon material.
[0039] In the present invention, the specific surface area of lignin hard carbon can be reduced by coating with petroleum coke pitch, and the first coulombic efficiency in sodium ion batteries can be improved. In detail: in the above preparation method, lignin is first converted into a first hard carbon precursor, which can prevent the by-products released by lignin during the subsequent coating and carbonization process from destroying the coating effect to a certain extent. Secondly, the first hard carbon precursor is mixed with a phosphorus source and a sulfur source, and after a second heat treatment, the surface of the first hard carbon precursor can be doped with more phosphorus and sulfur elements. Among them, on the first aspect, the phosphorus element has a high reactivity, and the doped phosphorus can react with the functional groups (such as hydroxyl, carboxyl, etc.) on the surface of the carbon material to form P-C, P-O bonds, etc. These chemical bonds can further enhance the bonding strength between the second hard carbon precursor and the petroleum coke pitch during the high-temperature carbonization process, making the interface between the two more stable. The sulfur atom has a large radius and is easy to form C-S, S-S and other bonds. Sulfur doping can also form carbon-sulfur bonds at high temperatures. This strong bonding can effectively enhance the interface bonding between the second hard carbon precursor and the petroleum coke pitch; on the second aspect, the phosphorus element has a high reactivity, and the doped phosphorus can react with the functional groups (such as hydroxyl, carboxyl, etc.) on the surface of the carbon material to form P-C, P-O bonds, etc. These chemical bonds can further enhance the bonding strength between the second hard carbon precursor and the petroleum coke pitch during the high-temperature carbonization process, making the interface between the two more stable. The sulfur atom has a large radius and is easy to form C-S, S-S and other bonds. Sulfur doping can also form carbon-sulfur bonds at high temperatures. This strong bonding can effectively enhance the interface bonding between the second hard carbon precursor and the petroleum coke pitch. Secondly, the doping of phosphorus and sulfur can introduce polar functional groups containing phosphorus and sulfur (such as phosphorus oxides and sulfur oxides). These functional groups can increase the polarity of the surface of the second hard carbon precursor, making the surface of the second hard carbon precursor easier to wet with petroleum coke asphalt, thereby improving the adhesion between the two. Thirdly, the doping of phosphorus and sulfur will also introduce defects on the surface of the second hard carbon precursor, forming more micropores or mesoporous structures, thereby enhancing the mechanical intercalation. During the heating process, the fluidity of petroleum coke asphalt increases at high temperatures, making it easier to fill into the pores or defects on the surface of the second hard carbon precursor caused by doping, thereby improving the interfacial bonding strength through mechanical intercalation. Finally, the second hard carbon precursor undergoes a third heat treatment to soften the petroleum coke asphalt and coat the surface of the second hard carbon precursor to form a coating layer, and then undergoes an oxidation treatment to increase the oxygen content in the asphalt. The oxygen content of the petroleum coke asphalt increases, and the rearrangement of carbon atoms prompts it to generate a carbon material that is difficult to graphitize during high-temperature carbonization. In the application of sodium ion batteries, the channel effect for the introduction and output of sodium ions can be improved.
[0040] In order to ensure the doping of phosphorus and sulfur, in an optional embodiment, in step S2, the first hard carbon precursor is mixed with a phosphorus source and a sulfur source, including the following process:
[0041] Grinding or stirring the first hard carbon precursor, the phosphorus source and the sulfur source to obtain the mixed system;
[0042] Alternatively, the first hard carbon precursor is dispersed in a solvent, and then a phosphorus source and a sulfur source are added for impregnation treatment. The solid product obtained by solid-liquid separation is dried to obtain the mixed system.
[0043] In an optional embodiment, the phosphorus source is phosphoric acid, disodium hydrogen phosphate or sodium tripolyphosphate; the sulfur source is thiourea, sodium sulfate or sodium sulfide.
[0044] Among them, phosphoric acid is an efficient and easily accessible phosphorus source with high reactivity. During the high-temperature carbonization process, it will generate phosphorus-containing functional groups and form a variety of phosphorus oxides such as P=O and P-O-C bonds, which are beneficial to further improve the surface polarity of carbon materials. In addition, the phosphorus oxide generated by phosphoric acid helps to improve the interfacial wettability and enhance the adhesion of petroleum coke pitch. At the same time, it forms a stable PC bond structure, which helps to improve the conductivity and chemical stability of hard carbon materials. Disodium hydrogen phosphate (Na2HPO4) has a moderate phosphorus content and has good dispersibility and water solubility as an inorganic salt, which is suitable for uniform doping. At the same time, its sodium element also helps to form active sites for sodium ion storage. During the high-temperature carbonization process, the phosphorus oxide generated by the decomposition of disodium hydrogen phosphate can provide excellent active sites, enhance the adsorption and storage capacity of hard carbon for sodium ions, and improve the capacity and cycle life of sodium ion batteries. Sodium tripolyphosphate (Na5P3O 10) is a chain phosphate with a high phosphorus content and is easy to form a uniform phosphorus distribution layer during high-temperature carbonization. Its structure is easy to decompose and release phosphorus to form a stable phosphorus oxide layer. Therefore, sodium tripolyphosphate can provide more doping sites. The generated phosphorus oxide layer can improve the specific surface area and pore structure of hard carbon materials, enhance the conductivity of the electrode and the sodium ion diffusion performance; thiourea (CH4N2S) decomposes during high-temperature carbonization to release sulfur and dope it into the carbon matrix, while producing a small amount of nitrogen source, which can achieve nitrogen-sulfur co-doping, help to form a variety of defect sites in the carbon matrix, and enhance the sodium Ion adsorption improves the sodium storage performance and conductivity of electrode materials. The decomposition temperature of thiourea is moderate and does not introduce other metal impurities, making it suitable for the preparation of high-purity hard carbon materials. Sodium sulfate (Na2SO4) is an economical and stable sulfur source. After thermal decomposition, it will produce sulfur oxides. These oxides help to form uniform sulfur doping at high temperatures, and sodium sulfate can also release a small amount of sodium, thereby further improving the conductivity of carbon materials. Sodium sulfide (Na2S) is easily decomposed into more active sulfur atoms during the carbonization process. At the same time, the generated sodium element can increase the conductivity and mobility of sodium ions in the carbon matrix.
[0045] In an optional embodiment, the molar ratio of the carbon element in the first hard carbon precursor to the phosphorus element in the phosphorus source and the sulfur element in the sulfur source is 100:3:1.
[0046] In order to further ensure the uniformity of heating of each raw material during heat treatment, in an optional embodiment, the Dv50 of the lignin is 3µm-15µm; the Dv50 of the petroleum coke asphalt is 2µm-7µm.
[0047] The above Dv50 represents the particle size value corresponding to 50% (by volume) of the cumulative amount in the particle size cumulative distribution curve, which is generally obtained by testing with a laser diffraction particle size distribution instrument.
[0048] In an optional embodiment, the time of the first heat treatment is 4h-6h, the time of the second heat treatment is 2h-4h, the time of the third heat treatment is 2h-6h, and the time of the fourth heat treatment is 2h-8h.
[0049] In an optional embodiment, step S3 uses a VCJ high temperature cladding machine to perform a third heat treatment.
[0050] In an optional embodiment, the petroleum coke pitch accounts for 1%-10% of the mass of the second hard carbon precursor.
[0051] The proportion of petroleum coke pitch affects the specific surface area and ion transmission capacity of the hard carbon material. The proportion of petroleum coke pitch within the above range can further ensure that the specific surface area of the hard carbon material is low, while ensuring that the thickness of the formed coating layer will not be too thick, which is beneficial to the complete oxidation of the petroleum coke pitch.
[0052] In an optional embodiment, the oxidation treatment includes the following process:
[0053] At a °C, perform a primary oxidation treatment for 1 min - 1 h;
[0054] At b °C, perform a secondary oxidation treatment for 1 h - 3 h;
[0055] At c °C, perform a tertiary oxidation treatment for 3 h - 5 h;
[0056] Wherein, a < b < c; and 150 ≤ a ≤ 200, 200 ≤ b ≤ 300, 300 ≤ c ≤ 400.
[0057] In the embodiment as described above, by controlling the temperature and time during the oxidation treatment, the oxygen content of the pitch is gradually increased without completely oxidizing it into a non-carbon-based material. This oxidation treatment method can effectively regulate the structural evolution of the pitch during the high-temperature carbonization process, thereby optimizing the final ion transport performance of the hard carbon material. Specifically, the primary oxidation treatment is carried out at a lower temperature for the preliminary oxidation of the petroleum coke pitch. The main function is to remove volatile components and slightly introduce oxygen content. The low-temperature stage can avoid excessive softening or melting of the petroleum coke pitch and maintain its physical structure. The short-time oxidation can form a preliminary oxidation layer on the surface of the petroleum coke pitch, which helps with subsequent deeper oxidation; the secondary oxidation treatment makes the chemical reaction of the petroleum coke pitch more intense by increasing the temperature, and oxygen elements can be more embedded into the petroleum coke pitch molecules to form oxygen-containing functional groups (such as carbonyl, hydroxyl, carboxyl, etc.). In this step, by controlling the oxidation time and temperature, over-oxidation can be prevented, and the oxygen content can be gradually adjusted. Prolonging the oxidation time allows oxygen atoms to gradually diffuse into the interior of the pitch to form a more uniform oxidation layer; the tertiary oxidation treatment further oxidizes at a higher temperature to promote the formation of a more stable oxygen-containing structure while restricting the melting of the petroleum coke pitch. This stage can ensure that the pitch is not easily formed into a graphitized structure during the subsequent carbonization process, and the holding time in this stage is relatively long, enabling the oxidation effect to proceed deeply, thereby adjusting the porosity and structure of the material.
[0058] In an optional embodiment, in the atmosphere of the primary oxidation treatment, the oxygen concentration is m, in the atmosphere of the secondary oxidation treatment, the oxygen concentration is n, and in the atmosphere of the tertiary oxidation treatment, the oxygen concentration is f, where m < n < f.
[0059] In the embodiment as described above, by controlling the oxygen concentration, partial oxidation of the pitch can be achieved, avoiding deterioration of the material performance caused by over-oxidation.
[0060] In an optional embodiment, the atmosphere can be controlled by intermittently injecting oxygen, allowing oxygen to alternate with an inert gas and combining it with a gradual increase in oxygen concentration, which can further avoid excessive oxidation of the asphalt while ensuring the controllability of the oxidation reaction.
[0061] Illustratively, the inert gas may be nitrogen and / or argon.
[0062] In an optional implementation, 5%≤m≤10%, 10%≤n≤20%, 20%≤f≤30%.
[0063] In an optional embodiment, step S2 further includes the following process: after adding an auxiliary agent to the mixed system, the oxidation treatment is performed; wherein the auxiliary agent is at least one of a sulfide, a metal oxide or a nitride, and the auxiliary agent accounts for 0.01%-0.1% of the mass of the mixed system.
[0064] In the above-mentioned implementation, the degree of oxidation can be further regulated by introducing auxiliary agents. For example, sulfides and nitrides can slow down the oxidation rate of asphalt and prevent it from being rapidly oxidized to completely oxygenated compounds; a small amount of metal oxides can promote moderate oxidation while limiting excessive oxidation.
[0065] In a second aspect, the present invention provides a hard carbon material obtained by the above preparation method.
[0066] In a third aspect, the present invention provides a battery, comprising an electrode sheet, wherein the electrode sheet comprises the hard carbon material described in the second aspect.
[0067] Exemplarily, the electrode sheet is a negative electrode sheet, which includes a current collector and a negative electrode slurry coated on the current collector, and the negative electrode slurry includes: the above-mentioned hard carbon material, a conductive agent, a binder and a solvent; the binder may include any one of polyvinylidene fluoride, polyvinyl pyrrolidone, sodium hydroxymethyl cellulose, sodium alginate and styrene-butadiene rubber, or a combination of at least two of them; the solvent may include any one of deionized water, N-methylpyrrolidone and anhydrous ethanol, or a combination of at least two of them; the conductive agent may include any one of conductive graphite, carbon nanotube conductive carbon black, acetylene black, Ketjen black, vapor-grown carbon fiber and expanded graphite, or a combination of at least two of them.
[0068] The present invention is further described below in conjunction with specific embodiments:
[0069] The CAS number of the lignin used in the following examples or comparative examples is 8068-05-1; the CAS number of petroleum coke pitch is 8052-42-4.
[0070] Example 1
[0071] This example provides a hard carbon material, and the preparation method thereof comprises the following steps:
[0072] S1: heating lignin (Dv50=5µm) to 1300°C at a heating rate of 5°C / min under a nitrogen atmosphere for 4 hours to obtain a first hard carbon precursor;
[0073] S2: The first hard carbon precursor and disodium hydrogen phosphate Na2HPO4 and sodium sulfate Na2SO4 are mixed in a molar ratio of carbon element, phosphorus element and sulfur source of 100:3:1, and the obtained mixed system is heated to 700°C at a heating rate of 5°C / min, and a second heat treatment is performed for 2h under a nitrogen atmosphere to obtain a second hard carbon precursor;
[0074] S3: Using VCJ high temperature coating, 1500g of the second hard carbon precursor and 75g of petroleum coke pitch (Dv50=3µm) were mixed. The obtained mixed system was heated to 350℃ at a heating rate of 2℃ / min under the protection of nitrogen, and stirred at a speed of 120rpm. After the third heat treatment for 2h, it was cooled to room temperature and then switched to nitrogen and oxygen mixed gas. The oxygen concentration was 5%, and the first oxidation treatment was carried out at 150℃ for 20min; the oxygen concentration was 20%, and the second oxidation treatment was carried out at 250℃ for 1h; the oxygen concentration was 30%, and the third oxidation treatment was carried out at 300℃ for 3h to obtain the third hard carbon precursor;
[0075] S4: The third hard carbon precursor is heated to 1400°C at a heating rate of 10°C / min under the protection of an inert gas, subjected to a fourth heat treatment for 4 hours, crushed, and sieved through a 300-mesh sieve to obtain a hard carbon material. Figure 1 This is a microscopic picture of the hard carbon material prepared in this example.
[0076] Example 2
[0077] The only difference from Example 1 is that the first treatment temperature is 1200°C; the second treatment temperature is 600°C; the third treatment temperature is 320°C, and the fourth treatment temperature is 1300°C.
[0078] Example 3
[0079] The only difference from Example 1 is that the first treatment temperature is 1500°C; the second treatment temperature is 800°C; the third treatment temperature is 400°C, and the fourth treatment temperature is 1500°C.
[0080] Example 4
[0081] The only difference from Example 1 is that step S3 is: using VCJ high-temperature coating, 1500g of the second hard carbon precursor and 75g of petroleum coke asphalt (Dv50=3µm) are mixed, and the obtained mixed system is heated to 350°C at a heating rate of 2°C / min under the protection of nitrogen, and stirred at a speed of 120rpm. After the third heat treatment for 2h, it is cooled to room temperature and then switched to a nitrogen and oxygen mixture with an oxygen concentration of 20%. At 150°C, the first oxidation treatment is carried out for 20min; at 250°C, the second oxidation treatment is carried out for 1h; at 300°C, the third oxidation treatment is carried out for 3h to obtain a third hard carbon precursor.
[0082] Comparative Example 1
[0083] The only difference from Example 1 is that step S1 is not performed, and disodium hydrogen phosphate Na2HPO4 and sodium sulfate Na2SO4 are directly mixed in a molar ratio of carbon element, phosphorus element and sulfur source of 100:3:1.
[0084] Comparative Example 2
[0085] The only difference from Example 1 is that step S2 is not performed, and the first hard carbon precursor and petroleum coke pitch are directly mixed.
[0086] Comparative Example 3
[0087] This example provides a hard carbon material, and the preparation method thereof comprises the following steps:
[0088] S1: heating lignin (Dv50=5µm) to 1300°C at a heating rate of 5°C / min under a nitrogen atmosphere for 4 hours to obtain a first hard carbon precursor;
[0089] S2: The first hard carbon precursor, disodium hydrogen phosphate Na2HPO4, and sodium sulfate Na2SO4 are mixed at a molar ratio of carbon element, phosphorus element, and sulfur source of 100:3:1 to obtain a mixed material;
[0090] S3: Using VCJ high temperature coating, 1500g of the above-mentioned mixed material and 75g of petroleum coke pitch (Dv50=3µm) were mixed, and the obtained mixed system was heated to 350°C at a heating rate of 2°C / min under the protection of nitrogen, and stirred at a speed of 120rpm. After the third heat treatment for 2h, it was cooled to room temperature and then switched to nitrogen and oxygen mixed gas. The oxygen concentration was 5%, and the primary oxidation treatment was carried out at 150°C for 20min; the oxygen concentration was 20%, and the secondary oxidation treatment was carried out at 250°C for 1h; the oxygen concentration was 30%, and the tertiary oxidation treatment was carried out at 300°C for 3h to obtain the third hard carbon precursor;
[0091] S4: The third hard carbon precursor is heated to 1400° C. at a heating rate of 10° C. / min under the protection of an inert gas, subjected to a fourth heat treatment for 4 h, crushed, and sieved through a 300-mesh sieve to obtain a hard carbon material.
[0092] Application Example 1
[0093] This example provides a series of electrode sheets, and the preparation method thereof comprises the following steps:
[0094] The hard carbon materials of each embodiment and comparative example were mixed with conductive carbon black (SP) and sodium carboxymethyl cellulose in a mass ratio of 95g:2g:3g, 200mL of water was added, and the mixture was stirred for 1h to obtain a mixed slurry. The mixed slurry was coated on a copper foil to obtain a coating with a thickness of 100μm. The mixture was vacuum dried at 100°C for 6h to obtain a series of electrode sheets.
[0095] Application Example 2
[0096] This example provides a series of sodium ion batteries, the preparation method of which includes the following steps:
[0097] The electrode sheet prepared in Application Example 1 was used as the positive electrode, sodium as the negative electrode, 1 mol / L NaPF6 was dissolved in ethylene carbonate (EC): dimethyl carbonate (DMC): propylene carbonate (PC) = 1:1:1, and 1 wt% fluoroethylene carbonate (FEC) was used as the electrolyte additive. The separator was glass fiber (GF / A). The battery was assembled in an argon-filled glove box and aged for 24 hours before charge and discharge tests were performed.
[0098] Characterization and testing
[0099] The specific surface area of each hard carbon material was tested by a BET analyzer, and the first coulombic efficiency (first efficiency) of each battery was obtained by testing with a battery test cabinet. The first coulombic efficiency % = first charge specific capacity / first discharge specific capacity × 100. The results are shown in Table 1.
[0100] Table 1:
[0101]
[0102] The above test results show that since the hard carbon materials of Examples 1-4 achieve better coating effects, the first coulombic efficiency of the assembled battery can be further improved compared with the comparative examples. Specifically, compared with Example 1, since the lignin in Comparative Example 1 has not been carbonized in step S1, volatile gases are released during the subsequent carbonization process, thereby causing the petroleum coke asphalt coating layer to be broken through by the released volatile gases, destroying the coating layer, resulting in poor coating effects, large specific surface area, and low first coulombic efficiency of the battery; compared with Example 1, since Comparative Example 2 does not add phosphorus and sulfur sources, the petroleum coke asphalt and the lignin carbon surface area are not well coated. The bonding ability of the surface is poor, resulting in poor coating effect, large specific surface area, and low first coulombic efficiency of the battery; compared with Example 1, since no second heat treatment is performed, disodium hydrogen phosphate and sodium sulfate are activated at high temperature to release volatile gases, which causes them to break through the asphalt coating layer in subsequent use, destroying the coating effect, and the first coulombic efficiency of the battery is low; and compared with Example 1 and Example 4, since the oxygen content is gradually increased in the oxidation treatment of Example 1, this oxidation treatment method can effectively regulate the structural evolution of asphalt during high-temperature carbonization, thereby optimizing the final ion transport performance of the hard carbon material, which is more conducive to improving the first coulombic efficiency of the battery.
[0103] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a hard carbon material, characterized in that: It includes the following steps: S1: Subject lignin to a first heat treatment at 1200°C - 1500°C to obtain a first hard carbon precursor; S2: Mix the first hard carbon precursor with a phosphorus source and a sulfur source, and subject the resulting mixture system to a second heat treatment at 600 - 800°C to obtain a second hard carbon precursor; S3: Mix the second hard carbon precursor with petroleum coke pitch, and subject the resulting mixture system to a third heat treatment at 320°C - 400°C under the protection of an inert gas, and then perform an oxidation treatment in an oxygen-containing atmosphere to obtain a third hard carbon precursor; S4: Subject the third hard carbon precursor to a fourth heat treatment at 1300°C - 1500°C under the protection of an inert gas to obtain the hard carbon material.
2. The preparation method according to claim 1, characterized in that: In step S2, the mixing of the first hard carbon precursor with the phosphorus source and the sulfur source includes the following process: Grind or stir the first hard carbon precursor, the phosphorus source, and the sulfur source to obtain the mixture system; Or, disperse the first hard carbon precursor in a solvent, then add the phosphorus source and the sulfur source, perform an impregnation treatment, and after drying the solid product obtained by solid-liquid separation, obtain the mixture system.
3. The preparation method according to claim 2, characterized in that: The phosphorus source is phosphoric acid, disodium hydrogen phosphate, or sodium tripolyphosphate; the sulfur source is thiourea, sodium sulfate, or sodium sulfide; And / or, the molar ratio of the carbon element of the first hard carbon precursor, the phosphorus element of the phosphorus source, and the sulfur element of the sulfur source is 100:3:
1.
4. The preparation method according to claim 1, characterized in that: The Dv50 of the lignin is 3 µm - 15 µm; the Dv50 of the petroleum coke pitch is 2 µm - 7 µm.
5. The preparation method according to claim 1, characterized in that: The petroleum coke pitch accounts for 1% - 10% of the mass of the second hard carbon precursor.
6. The preparation method according to claim 1, characterized in that: The oxidation treatment includes the following process: Perform a primary oxidation treatment for 1 min - 1 h at a°C; Perform a secondary oxidation treatment for 1 h - 3 h at b°C; Perform a tertiary oxidation treatment for 3 h - 5 h at c°C; Wherein, a < b < c; and 150 ≤ a ≤ 200, 200 ≤ b ≤ 300, 300 ≤ c ≤ 400.
7. The preparation method according to claim 6, characterized in that: In the atmosphere of the primary oxidation treatment, the oxygen concentration is m, in the atmosphere of the secondary oxidation treatment, the oxygen concentration is n, and in the atmosphere of the tertiary oxidation treatment, the oxygen concentration is f, and m < n < f.
8. The preparation method according to claim 7, characterized in that: 5% ≤ m ≤ 10%, 10% ≤ n ≤ 20%, 20% ≤ f ≤ 30%.
9. A hard carbon material, characterized in that: Prepared by the preparation method according to any one of claims 1 - 8.
10. A sodium ion battery, comprising an electrode sheet, characterized in that: The electrode sheet includes the hard carbon material according to claim 9.
Citation Information
Patent Citations
Negative electrode material and preparation method thereof, battery negative electrode and lithium ion battery
CN113422030A
Preparation method of biomass composite hard carbon negative electrode material, negative electrode material and application
CN115881919A